The policy implementation of corporation of consumer dispute resolution (BPSK) Reviewed from law number 8 year 1999 On consumer protection - Aditya Bagus Kuncoro (Legal Standing : Jurnal Ilmu Hukum, 2017)
The corporation of consumer protection plays an important role in the dispute resolutions that often occur in the community. Its existence is so beneficial for the middle class society who often becomes a dupe of injustice in the economic and business competition. However, in fact, the existence of a corporation of consumer disputes resolution in Indonesia does not have a serious attention from policy makers. The results of this study is that there is an imbalance in the regulation of central and local about the existence of this corporation of consumer dispute resolution. It is particularly on the issue of unclear funding arrangements and there is a misinterpretation between the central government and the regions. Therefore, the middle and the lower class society are not able to compete.